DESKRIPSI PENALARAN SPASIAL MAHASISWA CALON GURU BERGAYA BELAJAR VISUAL - Fiantika, Feny Rita; Kusmaharti, Dian; Rusminati, Susi Hermin (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2022)
Spatial thinking is a skill to remember, operate, manipulate, predict, combine, interpret, transform, explore an object to solve problems in various life contexts. Spatial thinking requires three related components, namely: the concept of space, spatial representation methods, and spatial reasoning. The difficulty of students for representing ideas encourages researchers to observe the spatial reasoning of elementary teacher training program’s student. Visual learning style is closely related to exact mathematical soul. Therefore, this study focuses on describing elementary teacher training program’ student’s visual learning style. The subjects of this research are students of class 2019 A and 2019 B as many as 70 elementary teacher training program’s student who are taking elementary school mathematics learning courses at a University in Surabaya and have been grouped into high, medium groups. and below. Medium group elementary teacher training program’s student were selected to be given a learning style test, which then described their spatial reasoning. The purpose of this study was to describe the reasoning of elementary teacher training program student’s visual learning style. This research is a descriptive qualitative research. Researchers used written test, geometry problem-solving questions, and interviews to explore in-depth information on students who are elementary teacher training program’s student of visual learning style. There are 40 students in the medium group with details of 10 students with visual learning style, 30 students with auditory learning style and 10 students with kinesthetic learning style. The group of students who are elementary teacher training program student’s visual learning style are analyzed for their spatial reasoning based on the results of written tests and interviews. The results showed that the visual learning style student’s group tended to work sequentially and neatly meeting the criteria for spatial reasoning indicators. Visual learning style of elementary teacher training program’s student (KSV) could describe their spatial reasoning through the process of categorizing, generalizing, synthesizing, evaluating, define, combine, and represent in solving geometric problems. One of the main characteristics of visual learning styles appears when they manipulate objects and illustrate with sketches. They carry out the work process in detail and detail, and represent through pictures or visuals